Analysis of Nutritional Intake, Infectious Diseases and Health Services on the Nutritional Status of Toddlers in the Working Area of Namtabung Health Center, Selaru District, Tanimbar Islands - Josefina Neltji Malisngorar; Nurwijayanti; Novita Ana Anggraini (STRADA : Jurnal Ilmiah Kesehatan, 2026)
Malnutrition among toddlers is still a public health problem in Indonesia. Malnutrition in toddlers can affect morbidity and mortality rates. The high level of morbidity in malnourished toddlers is caused by decreased energy. The body is resistant due to its inability to form antibodies in sufficient quantities. The macronutrient that functions to form antibodies is protein, apart from that protein is also needed for growth and development. Research by Erika, et al (2020) shows that malnourished toddlers do not consume protein according to their needs.